2020
DOI: 10.1111/ene.14462
|View full text |Cite
|
Sign up to set email alerts
|

Guillain–Barré syndrome associated with SARS‐CoV‐2 infection. A systematic review

Abstract: Guillain-Barr e syndrome (GBS) incidence can increase during outbreaks of infectious illnesses. A few cases of GBS associated with coronavirus disease 2019 (COVID-19) infection have been reported. The aim was to identify specific clinical features of GBS associated with COVID-19. PubMed, Embase and Cochrane were searched from 1 November 2019 to 17 May 2020 and included all papers with full text in English, Spanish, French or Italian, reporting original data of patients with GBS and COVID-19. Data were extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 40 publications
3
52
0
1
Order By: Relevance
“…Thus, it is not surprising to note the increasing number of reports on COVID-19 patients with acute immune-mediated like neurologic signs and symptoms, published in the literature since the beginning of the pandemic. A recent systematic review showed that published cases of GBS induced by SARS-CoV-2 reported mostly a sensorimotor, demyelinating GBS with a typical clinical presentation, which is similar to GBS cases due to other etiological factors [ 82 ]. Table 9 summarizes the case reports/series identified through our research strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is not surprising to note the increasing number of reports on COVID-19 patients with acute immune-mediated like neurologic signs and symptoms, published in the literature since the beginning of the pandemic. A recent systematic review showed that published cases of GBS induced by SARS-CoV-2 reported mostly a sensorimotor, demyelinating GBS with a typical clinical presentation, which is similar to GBS cases due to other etiological factors [ 82 ]. Table 9 summarizes the case reports/series identified through our research strategy.…”
Section: Resultsmentioning
confidence: 99%
“…The most recent review paper by Abu-Rumeileh et al is also the most extensive, which included 73 cases [ 3 ]. It included most of the cases reviewed in the other seven review papers that were published prior [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Only two additional cases have been identified by a shorter review paper by Ellul et al [ 7 ].…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…Searches were performed cross referencing the following key terms “Covid-19”, “Guillain Barre”, “Miller Fisher”, “GM1”, “GQ1b”, and “Ganglioside”. Of the 102 articles found eight were large scale review papers [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]; the other entries were all case reports. All cases included in the eight review papers and each separate case studies were reviewed.…”
Section: Methodsmentioning
confidence: 99%
“…All reported patients in this study received intravenous immunoglobulin (IVIg) except for two (88.9%); while one underwent plasma exchange after IVIg therapy. [13] . Here, we reported three cases of GBS during the active phase of COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%